The Effect Of Artificial Fish Feed From Organic Waste On Fish Cultivation In The Maritime Region - Hutajulu Ezra Solafide; Fitriani Putri; Natasha Febiana; Pohan Anggi Amanda (SHS Web of Conferences)
The Riau islands preserve the potential for raising large fisheries cultivation in the maritime region. One of the components that support fisheries cultivation is fish feed. In this globalization, feed is increasingly expensive and must be imported. This is what makes the fisheries farmers struggle to produce fish because they can only buy feed in smaller portions than they should. Innovation in place of feed by using the anchovies, coconut dregs and banana husks, which are safely consumed and created with specific formulations based on the nutritional needs of the fish, has the purpose to overcome expensive feed costs and create a clean and healthy environment. This research is a qualitative study with an experiment method. The result would be an increase in fisheries production due to solving the economic problems. Hence, the existence of artificial feed with economic value can provide great opportunities in cultivation and maritime business.